Estimation the Level of Metals (Lead, Cadmium, Copper and Zinc) In Multiple Sclerosis Patients in Basra Iraq - Ali Diame Nashmi 1 , Ali Faris Hassan2 , Mazin Mohamed Hammady3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Multiple sclerosis (MS) is a demyelinating inflammatory disease of the central nervous system white matter that displays a triad of pathogenic symptoms. The toxicity of heavy metals can disrupt or damage central nervous systems. Long-term exposure of human population to heavy metals has shown neurological impairments. The degenerative processes are similar to Alzheimer’s disease; Parkinson’s disease.This study compared the serum level of Lead, Cadmium, Copper and Zinc in MS patients with their levels in a control group. Methods: prospective study of cohort includes fifty Iraqi people selected from the Southern area of Multiple Sclerosis Clinic Center divided into two groups, in which the first group contains twenty five patients with MS and twenty five people without MS. Serum level of Lead, Cadmium, Copper and Zinc have been measured. Results:In the present study, there was a significant increase in the concentration of (cupper - lead –cadmium) in patients with multiple sclerosis as compared with normal people (p<0.05). There is a significant decrease in the concentration of zinc in patients with multiple sclerosis as compared with normal people (p<0.05).Conclusion: Lead, copper, cadmium and zinc could affect on the susceptibility of patients to induce MS attack.